Predictive factors for clinically significant pharmacist interventions at hospital admission. Issue 9 (March 2018) - Mongaret, Céline; Quillet, Pauline; Vo, Thi Ha; Aubert, Léa; Fourgeaud, Mathieu; Michelet-Huot, Elise; Bonnet, Morgane; Bedouch, Pierrick; Slimano, Florian; Gangloff, Sophie C.; Drame, Moustapha; Hettler, Dominique
Abstract : Abstract: Pharmaceutical care activities at hospital admission have a significant impact on patient safety. The objective of this study was to identify predictive factors for clinically significant pharmacist interventions (PIs) performed during medication reconciliation and medication review at patient hospital admission. A 4-week prospective study was conducted in 4 medicine wards. At hospital admission, medication reconciliation and medication review were conducted and PIs were performed by the pharmaceutical team. The clinical impact of PIs was determined using the clinical economic and organizational (CLEO) tool. Clinical characteristics, laboratory results, and medication data for each patient were collected and analyzed as potential predictive factors of clinically significant PIs. Univariate and multivariate binary logistic regression were subsequently used to identify independent predictive factors for clinically relevant PIs. Among 265 patients admitted, 150 patients were included. Among 170 PIs performed at hospital admission, 71 were related to unintentional discrepancies (41.8%) during medication reconciliation, and 99 were related to drug-related problems (DRPs) (58.8%) during medication review. Overall, 115 PIs (67.7%) were considered to have a clinical impact. By multivariate analysis, number of medications ≥5 ( P = .01) based on the best possible medication history, and Charlson comorbidity index score ≥2 ( P < . 01) were found to be independent predictive factors of clinically significant PIs at hospital admission. Identifying predictive factors of clinically significant PIs is valuable to optimize clinical pharmacist practices at hospital admission during both medication reconciliation and medication review. These 2 steps of the pharmaceutical care process improve medication safety at hospital admission. Abstract : Supplemental Digital Content is available in the text